05 Core-shell medicated nanoparticles prepared using coaxial electrospray for fast dissolution of paracetamol. (5th December 2017) - Li, HP; Zhang, LL; Zhang, YY; DG, Yu
Abstract : Background: The dissolution of insoluble drugs is one of the most intractable challenges in pharmaceutics, particularly for those used to rapidly bring down a fever or stop pain. Advanced technologies are frequently introduced into this field for developing nano drug delivery systems (DDS) for this purpose. Methods: Coaxial electrospray is a popular advanced process for creating core-shell micro-/nano-structures. Here, a core-shell nano DDS was fabricated and characterised in detail for enhancing the fast dissolution of paracetamol. A surfactant solution (consisting of 0.5% w/v Triton X-100% and 10% w/v polyvinylpyrrolidone (PVP) K10 in ethanol) and a drug solution (composed of 5% w/v paracetamol and 10% w/v PVP K10 in ethanol) were exploited. Results: Under the selected conditions (an applied voltage of 20 kV, a collecting distance of 15 cm, and a shell-to-core fluid flow rate ratio of 0.5/1.5 mL/h), uniform core-shell nanoparticles were stably and continuously fabricated. Owing to the secondary interactions between PVP and paracetamol, the particles were amorphous composites, as verified by the XRD patterns and attenuated total reflectance–FTIR spectra. The nanoparticles could release the loaded cargoes within one minute after they were placed into the dissolution media. Conclusion: Core-shell medicated nanoparticles prepared using coaxial electrospray can be an alternative approach for improving the dissolution rate of insoluble drugs. Acknowledgements: Supported by the National Natural Science Foundation of China (No. 51373101).